2001
DOI: 10.1115/1.1409262
|View full text |Cite
|
Sign up to set email alerts
|

Modeling of Heat Transfer in a Mist/Steam Impinging Jet

Abstract: The addition of mist to a flow of steam or gas offers enhanced cooling for many applications, including cooling of gas turbine blades. The enhancement mechanisms include effects of mixing of mist with the gas phase and effects of evaporation of the droplets. An impinging mist flow is attractive for study because the impact velocity is relatively high and predictable. Water droplets, less than 15 μm diameter and at concentrations below 10 percent, are considered. The heat transfer is assumed to be the superposi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(23 citation statements)
references
References 17 publications
1
18
0
Order By: Relevance
“…Models of collisions and coalescences will also be developed and incorporated into the future studies. Li et al modeled the mist cooling [22] using the experimental data from [13] and reported the major contribution for mist cooling enhancement was from the direct contact between droplets and the wall. In this paper, the direct droplet-wall contact heat transfer mechanism is not included, so the cooling results could be probably 50% under predicted.…”
Section: Concerns and Future Researchmentioning
confidence: 99%
“…Models of collisions and coalescences will also be developed and incorporated into the future studies. Li et al modeled the mist cooling [22] using the experimental data from [13] and reported the major contribution for mist cooling enhancement was from the direct contact between droplets and the wall. In this paper, the direct droplet-wall contact heat transfer mechanism is not included, so the cooling results could be probably 50% under predicted.…”
Section: Concerns and Future Researchmentioning
confidence: 99%
“…The heat transfer between an individual droplet and wall is eventually related to the surface superheat, droplet diameter, impact velocity, and droplet surface tension. The comprehensive modeling and evaluations of q 00 1 , q 00 2 , and q 00 3 can be found in [7]. Depending on the mist flow conditions, heat conduction between the droplets and heated surface ðq 00 3 Þ and the subsequent liquid evaporation contribute about 80-99% to the total enhancement ðq 00 2 þ q 00 3 Þ.…”
Section: Resultsmentioning
confidence: 99%
“…Detailed mist/steam heat transfer mechanisms were investigated and analyzed by Li et al [7], in which the overall heat transfer of mist/steam is divided into three parts: heat transfer from the target wall to the steam flow ðq 00 1 Þ, heat transfer between steam and droplets (quenching effect, q 00 2 ), and heat transfer from wall to droplets ðq 0 3 Þ. Therefore, the enhancement ratio can be given as…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Li. et al [34] analytically showed that the brief contact between the droplet and the wall plays a major role in transferring heat. Rather than correctly model the droplet-wall interactions, the "trap" wall condition is applied for comparison.…”
Section: Mist/air Film Cooling At Gas Turbine Operating Conditionsmentioning
confidence: 99%